Resources Provision of Rural Territories Social Sphere: A Case Study - RUBAEVA, Olga; POGARTSEVA, Ekaterina; KOT, Ekaterina; NIKITINA, Tatyana (Journal of Environmental Management and Tourism; Vol 9 No 7 (2018): JEMT Volume IX Issues 7(31) Winter 2018DO - 10.14505//jemt.9.7(31).15, 2019)
The article presents analysis of resources provision of social sphere of the rural territories of Chelyabinsk region; there are analyzed the main components of creature comforts of a rural population.  There is given an assessment of a program implementation of sustainable development of the rural territories of Chelyabinsk region and the country in general. There are the numerical data characterizing the delivery of Program in regions of the Russian Federation and amounts of financing for realization the actions contributing to sustainable development of the rural territories. The main directions of the Program are connected with providing the rural territories with a necessary social infrastructure sufficient for maintenance of worthy level of living of a rural population and also to promoting growth of appeal of shape of the rural territories to inflow of the human and investment equities. There is shown an international experience of achievement of high level and quality of life in the rural territories. There are determined the main priorities of development of the rural territories of the European countries: innovation in the structuring of farming; providing a continuous line of production of producing agricultural products; rational use of natural resources; improvement of social and economic conditions of life sustenance in the rural territories. There is revealed the direct dependence between ensuring growth of sustainable development level of the rural territories on degree of a scope and efficiency of use of own resources and the available potentials in the territories. Here are allocated types of the rural territories on the level of sustainable development: the territories of the advancing development; the developing territories; survival territories. There are established the reasons of decrease in life level in the rural territories and great lagging from the level of sustainable development of urban localities. The main reasons are: the concentration of production and conversion of agricultural products in certain settlements promoting desolation and irrational use of potentials of other territories; insufficient financing of the social sphere; a lack of support from the state of small-scale farmer and personal subsidiary farms. There are made recommendations about enhancement of organizational, economic and ecological opportunities of use of the available resource providing the rural territories; production organizations of agricultural products; development of a social infrastructure.